A synthesis of star calibration techniques for ground‐based narrowband electron‐multiplying charge‐coupled device imagers used in auroral photometry. Issue 6 (21st June 2016) - Grubbs, Guy; Michell, Robert; Samara, Marilia; Hampton, Don; Jahn, Jorg‐Micha
Abstract: A technique is presented for the periodic and systematic calibration of ground‐based optical imagers. It is important to have a common system of units (Rayleighs or photon flux) for cross comparison as well as self‐comparison over time. With the advancement in technology, the sensitivity of these imagers has improved so that stars can be used for more precise calibration. Background subtraction, flat fielding, star mapping, and other common techniques are combined in deriving a calibration technique appropriate for a variety of ground‐based imager installations. Spectral (4278, 5577, and 8446 Å) ground‐based imager data with multiple fields of view (19, 47, and 180°) are processed and calibrated using the techniques developed. The calibration techniques applied result in intensity measurements in agreement between different imagers using identical spectral filtering, and the intensity at each wavelength observed is within the expected range of auroral measurements. The application of these star calibration techniques, which convert raw imager counts into units of photon flux, makes it possible to do quantitative photometry. The computed photon fluxes, in units of Rayleighs, can be used for the absolute photometry between instruments or as input parameters for auroral electron transport models. Key Points: This technique shows a robust way to calibrate optical imagers while they are deployed Star calibration allows for increased accuracy of measurements and systematic instrument inspection The computed photon fluxes can be used as input parameters for auroral electron transport models